2023
DOI: 10.1111/psyp.14443
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin is related to lower brain reward activation during touch

D. M. Pfabigan,
E. R. Frogner,
E. Schéle
et al.

Abstract: The gut hormone ghrelin drives food motivation and increases food intake, but it is also involved in the anticipation of and response to rewards other than food. This pre‐registered study investigated how naturally varying ghrelin concentrations affect the processing of touch as a social reward in humans. Sixty‐seven volunteers received slow caressing touch (so‐called CT‐targeted touch) as a social reward and control touch on their shins during 3T functional imaging on two test days. On one occasion, participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
2
3
0
Order By: Relevance
“…In our study, we also invited participants to rate the pleasantness of the touch they received. Consistent with prior research (Ali et al, 2023;Pfabigan et al, 2023;van Hooijdonk et al, 2019;von Mohr et al, 2017;Zheng et al, 2021), our participants reported higher levels of pleasantness when the touch was administered at the CT-optimal speed and when delivered by a human rather than an artificial hand. Crucially, self-reports mirrored pupil results by revealing that participants reported the highest ratings of pleasantness when tactile stimulation featured both CT-optimal speed and human contact simultaneously.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we also invited participants to rate the pleasantness of the touch they received. Consistent with prior research (Ali et al, 2023;Pfabigan et al, 2023;van Hooijdonk et al, 2019;von Mohr et al, 2017;Zheng et al, 2021), our participants reported higher levels of pleasantness when the touch was administered at the CT-optimal speed and when delivered by a human rather than an artificial hand. Crucially, self-reports mirrored pupil results by revealing that participants reported the highest ratings of pleasantness when tactile stimulation featured both CT-optimal speed and human contact simultaneously.…”
Section: Discussionsupporting
confidence: 89%
“…From an evolutionary perspective, it could be hypothesized that ghrelin would not simply increase sensitivity to all rewards and decrease sensitivity to all negative outcomes. This is supported by the recent report of decreased hedonic responses to affective touch during higher amounts of ghrelin [ 59 ]. However, monetary rewards are domain-general, as they can be used to gain any type of reward, not just food.…”
Section: Discussionsupporting
confidence: 80%
“…Within the VMH, the increase in fluorescent ghrelin binding and c- fos expression were primarily observed in the ventrolateral portion, a subregion in the VMH that is linked to social behaviors that include mating and aggression in mice, and not with metabolic function ( Lin et al, 2011 ; Falkner et al, 2016 ; Flanigan and Russo, 2019 ). Ghrelin has been linked to behavioral responses with a social component, and some have suggested that ghrelin may play a role in maintaining social behaviors ( Park et al, 2021 ; Pfabigan et al, 2024 ), and resilience in general, in the face of significant stressors like the stress experienced by socially defeated mice ( Lutter et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%